A bicriteria model for production planning in a toothpaste factory (2012)
This paper presents a bicriteria formulation of the material allocation to production facilities problem. The system under consideration is a toothpaste factory. Two objectives of the factory were identified, namely; (i) Minimization of the total sum of processing costs (ii) Maximization of the capacity utilization of production facilities. Linear Combination of Objective Functions (LCOF) method was used to solve the problem for the situation where the objectives were of equal importance. The solutions were compared to that of goal programming (GP) and they were found to be identical. The least utilized production facility was processing plant 1 with utilization of 20.32% followed by filling machine 1 with utilization of 43.85%. All the other production facilities were operated at 100% capacity. For LCOF, one problem was solved to obtain the solution while in the case of GP three problems were solved. LCOF is superior to GP in terms of simplicity and time savings.